Sexuality and Being in the Poststructuralist Universe of Clarice Lispector : The Différance of Desire - Fitz, Earl E. (Book collections on Project MUSE., 2001)
This book argues that poststructuralism offers important and revealing insights into all aspects of Lispector's writing.